Do CEO characteristics moderate the link between CEO power and firm performance? - Liandy, Veirent Audrew; Mahfirah , Titis Fatarina; Lajuni, Nelson (Ifma Publishing, 2024)
This study investigated the impact of CEO power on firm performance. Additionally, the moderating role of CEO age, gender and education on the relationship between CEO power and firm performance was investigated. This study uses panel data from the Indonesia Stock Exchange in the 2018-2022 period. This study utilized a purposive sampling technique to obtain 320 observations. The findings showed that the level of CEO power did not have a significant influence on firm performance. CEO gender was proven to have a positive influence in moderating the relationship between CEO power and firm performance (Tobin's Q). .